PENGUKURAN BEBAN KERJA OPERATOR CRANE DENGAN METODE NASA-TLX DI PELABUHAN KHUSUS CNOOC SES - Jutika Cahyana, Babay; Rujito (ISTA Online Technologi Journal, 2022)
Abstract The problem raised in this study is how the mental load experienced by the crane pedestal operator can be measured using the National Aeronautics and Space Administration Task Load Index (NASA-TLX) method. To then take control measures to reduce or eliminate the mental burden when operating a pedestal crane so that the factor of work accidents when operating a pedestal crane can be eliminated or reduced. The results showed one worker with a very high workload and three workers with a high workload. The element that has the level of influence on the workload is the element of effort with an average value of 23.3. By looking at the results of data processing and the high level of workload on all workers which can affect the work system to be less good, it is necessary to take countermeasures and improvements so that the possibility of work accidents can be eliminated or reduced Keywords: Mental load, NASA-TLX, Pedestal crane